The Influence of Radical Islam on the Quality of Islamic Education in Schools - Subhan Hi Ali Dodego; Arisatul Muwafiqoh; Buya Hamka; Maulana Aminudin (Sustainable, 2022)
This paper discusses the influence of radical Islamic understanding on the quality of Islamic education in schools. The method used in this research is qualitative. While the data collection technique is literature. The results of this study indicate that. First, the notion of radicalism in Islam is an understanding that wants radical changes in both the individual, social, political and religious domains. The understanding of religious radicalism wants a fast and revolutionary change by using exclusive, extreme, fundamentalist methods and finally terrorizing opponents who do not agree with them. Interpreting the verses of the Qur’an and hadith is done textually and according to their wishes. Second, currently the influence of radicalism has targeted and entered into Islamic education in schools. The survey results of several institutions indicate that the influence of radicalism and intolerance is included in the realm of Islamic education. The influence of radical understanding in the world of Islamic education today is through various ways, it could be from the teachers, the learning curriculum in schools, learning methods, textbooks to the inclusion of mass media platforms. Third, deradicalization of radicalism in Islamic education needs to be done to ward off radicalism, such as parents and the community jointly preventing the rise of cases of radicalism in the world of education.